Exploring the Social Media Health Information Seeking Patterns of Rural Residents to Provide Communication Strategies for Extension - Catherine Sanders; Kristin Gibson; Allison R Byrd; Tatevik Markosyan; Alexa J. Lamm (Journal of Applied Communications, 2023)
Communication capacity development is critical for Extension professionals, who work to bring agricultural and health research to the public. With social media being an almost ubiquitous communication channel, it has immense potential as a health communication resource for diverse and rural audiences. The current study, guided by an audience segmentation framework, explored the health communication patterns on social media of rural Georgia residents across demographic characteristics through a non-probability opt-in sampling online survey. Cluster analyses of social media users revealed three distinct groups: low, medium, and high users. Descriptive characteristics of each cluster were presented, to guide Extension health communication practices in rural Georgia. Additionally, inferential statistics revealed a relationship between cluster membership and perceptions of health information on social media: high frequency users were more likely to positively perceive the health information, while low users were more likely to negatively perceive the information. Implications for health promotion and Extension practitioners include using audience segmentation strategies to increase the effectiveness of tailored messages to enhance the success of social media communication for rural residents.
Keywords: cluster analysis; health communication; audience segmentation; Extension; rural outreach